Clinoenstatite coatings have high bonding strength, bioactive ion release, and osteoimmunomodulatory effects that enhance in vivo osseointegration. (December 2015) - Wu, Chengtie; Chen, Zetao; Wu, Qianju; Yi, Deliang; Friis, Thor; Zheng, Xuebin; Chang, Jiang; Jiang, Xinquan; Xiao, Yin
Abstract: A number of coating materials have been developed over past two decades seeking to improve the osseointegration of orthopedic metal implants. Despite the many candidate materials trialed, their low rate of translation into clinical applications suggests there is room for improving the current strategies for their development. We therefore propose that the ideal coating material(s) should possess the following three properties: (i) high bonding strength, (ii) release of functional ions, and (iii) favourable osteoimmunomodulatory effects. To test this proposal, we developed clinoenstatite (CLT, MgSiO3 ), which as a coating material has high bonding strength, cytocompability and immunomodulatory effects that are favourable for in vivo osteogenesis. The bonding strength of CLT coatings was 50.1 ± 3.2 MPa, more than twice that of hydroxyapatite (HA) coatings, at 23.5 ± 3.5 MPa. CLT coatings released Mg and Si ions, and compared to HA coatings, induced an immunomodulation more conducive for osseointegration, demonstrated by downregurelation of pro-inflammatory cytokines, enhancement of osteogenesis, and inhibition of osteoclastogenesis. In vivo studies demonstrated that CLT coatings improved osseointegration with host bone, as shown by the enhanced biomechanical strength and increased de novo bone formation, when compared with HA coatings. These results support the notion that coating materials with the proposed properties can induce an in vivo environment better suited for osseointegration. These properties could, therefore, be fundamental when developing high-performance coating materials.